Characterisation of potential interactions between urease inhibitor N-(n-butyl) thiophosphoric triamide (NBPT) and whey protein isolate - Maria P. Byrne; Patrick J. Forrestal; Tom F.O' Callaghan; Niharika Rahman; Aishwarya Ray; Martin Danaher; Bernard M. Corrigan; Chikere G. Nkwonta; Karl Richards; Farhad Garavand; Enda Cummins; Sean A. Hogan (Food Chemistry: X, 2025)
Urea fertilizer augmented with the urease inhibitor (UI) N-(n-butyl)-thiophosphoric triamide (NBPT), is used to stabilize nitrogen and reduce greenhouse gas emissions. Although studies have shown that NBPT does not enter milk via cattle grazing on NBPT-treated fields, questions remain about its potential to impact milk components were it inadvertently to enter the dairy supply chain. The aim of this study was to examine possible effects of NBPT on the chemistry and functionality of whey protein isolate (WPI). NBPT raised the peak denaturation temperature of WPI (p < 0.05) and resulted in increased hydrogen bonding and β-sheet formation. NBPT reduced the viscosity of WPI and caused faster gelation. NBPT had a competitive adsorption advantage at the air-water interface (p < 0.05) compared to WPI. Microscopy imaging of WPI-NBPT gels revealed increased protein aggregation. Overall, NBPT modified the structure and functionality of WPI, primarily through non-covalent interactions.